Australian final year nursing students′ and registered nurse supervisors' perceptions of a gerontology clinical learning experience: A preliminary appraisal. (July 2018) - Ryan, Colleen; Ellem, Pammie; Heaton, Leeanne; Mulvogue, Jennifer; Cousins, Marina; De George – Walker, Linda
Abstract: Current international research suggests universities providing nursing education should focus on shifting students' attitudes towards valuing clinical learning derived from aged care settings, offering support and education for aged care facility staff supervising nursing students' learning in the aged care setting, and encouraging nursing graduates to consider pursuing careers in gerontology nursing. Against this international backdrop, one Australian School of Nursing designed a structured clinical learning experience to offer final year nursing students an opportunity to further their knowledge and understanding of the complexities of the role of the gerontology registered nurse. Additionally, this clinical learning experience included provision for nursing academics to offer support and expertise to the aged care facility staff around the role of supervising and assessing final year nursing students' clinical learning. The aim of this paper is to present fifteen final year nursing students' and nine registered nurse supervisors' evaluations of the gerontology clinical learning experience and the success of the learning experience towards meeting the project aims. Mostly participants reported positive experiences and agreed the experience illuminated the role of the gerontology registered nurse. Participants in this study also provided suggestions about the benefits and barriers of the clinical learning experience. Highlights: Gerontology clinical learning is beneficial for final year nursing students. Gerontology RN requested further education around clinical supervision. A clinical learning model guided students and RN's.